Risks assessment of using artificial intelligence in education - Jelica,; Sofija, (Sociološki pregled, 2025)
Recognising ethical challenges in integrating artificial intelligence in education raises many sociological questions. This study aims to identify and classify risks of using artificial intelligence in education with a quantitative assessment of the probability of risk occurrence in relation to the degree of teacher control and artificial intelligence automation according to the Human-Centred model. The theoretical analysis identified 10 risks, which were grouped into four categories. The descriptive statistical analysis based on insights from nine experts indicates that a combination of high control and high automation is most effective in mitigating risks, whereas low control with high automation is the riskiest scenario. Future implications emphasise preventive educational measures for reliable use.
Keywords: teacher control; artificial intelligence automation; educational risks; digital society; hybrid intelligence